Effectiveness of Home Care Nursing Program (HCNP) on The activities of daily living of stroke patients - Samsiah M; Santhna L. P; Hamidah H; Ruth P.R.D (Penerbit UKM, 2007)
Home Care Nursing Program (HCNP) at HUKM was started in 1998 and evaluation of the program was required. The objective of this study is to evaluate the effectiveness of HCNP on stroke rehabilitation at HUKM. A retrospective study using a matched pair design involving 69 stroke patients admitted to HUKM from August 1998 to December 2000 was carried out. The participants of this study were the HCNP group (n=35), and Non- HCNP (n=34). The matching was based on five criteria; age, sex,race, data of admission and severity of disability. The HCNP group was identified through data at the HCNP unit and their medical reports were traced. For the Non-HCNP group, the participants were identified based on criteria which were similar to that of the HCNP group. Based on the criteria identified, there was no significant difference between the two groups. The Activities of Daily Living was measured using the Modified Barthel Index twice; once on admission (based on record) and one post stroke. The t-test was applied to parametric data and non-parametric data; Chi-square was used to detect any significant relationships between the scores of the two groups. Results showed no significant difference (p=0.1990) in ADL on admission and ADL post stroke patients between the two groups. However, there were significant difference (HCNP p=0.000 and Non-HCNP p=0.000) in ADL on admission and post stroke for stroke patients who sought alternative treatment compared to those who had not